Efek Fermentasi Basah Menggunakan Kultur Saccharomyces cerevisiae Terhadap Sifat Kimia dan Sensori Kopi Robusta (Coffea canephora) - Larassati, Dyah Putri; kustyawati, maria erna; sartika, dewi; AS, suharyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
High levels of caffeine in Robusta coffee beans can be reduced by Wet coffee fermentation. Saccharomyces cerevisiae an excellent hydrolytic enzyme producer has important role in food fermentation. This study aims to determine the interaction between the addition of Saccharomyces cerevisiae and fermentation time on the chemical and sensory properties of the coffee produced. This research was conducted using a complete randomized block design factorial with two factors. The first factor is was the coffee fermentation time (T) consisting of four levels, 12(T1), 24(T2), 36(T3) and 48(T4) hours. The second factor was the addition of Saccharomyces cerevisiae culture consisting of three levels, without the addition of culture (S0), addition of 1% S. cerevisiae culture (S1), and the addition of 3% S. cerevisiae culture (S2). Further data analysis was done by using the Orthogonal Polynomial test. The best results in this study was the addition of 1% Saccharomycess cerevisiae and 48 hours of fermentation time producing the ground coffee with a water content of 6.43%, an ash content of 4.49%, a taste score of 3.17 (rather typical of coffee), a score aroma of 2.83 (somewhat typical of coffee), overall acceptance of 3.00 (somewhat typical of coffee), caffeine content of 23463.58 mg / kg and chlorogenic acid of 31769.80 mg. It can be concluded that S.cerevisiae cultured in wet coffee fermentation reduced the caffeine level of Robusta coffee and was a potential culture used for wet coffee fermentation. Keywords: coffee fermentation, fermentation time, Robusta, Saccharomyces cerevisiae